Differential effects of glycation on protein aggregation and amyloid formation - Iannuzzi, Clara; Irace, Gaetano; Sirangelo, Ivana (Frontiers in Molecular Biosciences, 2014)
Amyloids are a class of insoluble proteinaceous substances generally composed of linear un-branched fibrils that are formed from misfolded proteins. Conformational diseases such as Alzheimer’s disease, transmissible spongiform encephalopathies, and familial amyloidosis are associated with the presence of amyloid aggregates in the affected tissues. The majority of the cases are sporadic, suggesting that several factors must contribute to the onset and progression of these disorders. Among them, in the past ten years, non enzymatic glycation of proteins has been reported to stimulate protein aggregation and amyloid deposition. In this review, we analyze the most recent advances in this field suggesting that the effects induced by glycation may not be generalized as strongly depending on the protein structure. Indeed, being a post-translational modification, glycation could differentially affects the aggregation process in promoting, accelerating and/or stabilizing on-pathway and off-pathway species.